A Novel Crystal Modified Electrode Based on Cs4PW11Fe: Comparative Study of Its Electrochemical Behavior and Electrocatalysis. Issue 6 (9th April 2020) - Li, Lina; Ma, Jian; Li, Xiaoshan; Ma, Hang; Liu, Jiahao; Huang, Yanqing; You, Chenghang; Liu, Xilong; Hua, Yingjie; Wang, Chongtai
Abstract : Here reports a novel Cs4 PW11 Fe crystal modified electrode (CME), which was prepared by in situ growing Cs4 PW11 Fe crystals on the surface of a graphite electrode in a simple hydrothermal process. The as-prepared Cs4 PW11 Fe CME presents a much better electrocatalytic performance for H2 O2 reduction compared to the reported previously (Bu4 N)4 PW11 Fe CME and the PW11 Fe/CS ME due to possessing the quasi-square single crystals orderly stacking on the surface of the graphite electrode. The current density of H2 O2 reduction at the Cs4 PW11 Fe CME is 425 μ A·cm −2, far higher than that at the (Bu4 N)4 PW11 Fe CME and at the PW11 Fe/CS ME. The kinetic parameter k of H2 O2 reduction at the Cs4 PW11 Fe CME was estimated to be 9.1 × 10 −4 cm·s −1 in term of the Koutecký-Levich equation. The electrocatalysis occurs through a "Fe(II)-H2 O2 " transition state mechanism.